Faktor-Faktor Yang Mempengaruhi Produktivitas Kerja Karyawan Panen Kelapa Sawit PT. Agronusa Bumi Lestari di Desa Mendis Jaya Kecamatan Bayung Lencir Kabupaten Musi Banyuasin - Oktaviani, Evi; Asmaida, Asmaida; Wulandari, Siti Abir (Universitas Batangahari Jambi, 2025)
The purpose oh this study is to analyze the factors that influence the work productivity of oil palm harvest employees at PT. Agronusa Bumi Lestari in Mendis Jaya Village. Field conditions show differences in productivity levels among harvest employees, which are suspected to be influenced by factors such as age, years of service, number of dependents, commuting distance, wages, and level of education. Data collection was carried out in June 2025. The sample in this study consisted of 41 harvest employees selected using the census method. This study employs cross sectional data collected at a specific point in time with a ratio measurement scale, obtained from both primary and secondary sources. The collected data were analyzed descriptively and quantitatively using multiple linear regression methods. Based on the research findings, the average productivity of harvest employess at PT. Agronusa Bumi Lestari in Mendis Jaya Village is 32.044 kg/person/month. As much as 90.3% of the variation in the variable of age, years of service, number of dependents, distance traveled, wages, and education level can be explained by the model, while yhe remaining portion is accounted for by other variables. The simultaneous test indicate that these factors collectively have a significant effect on the work productivity of oil palm harvest employees. The partial test result show that years of service (X_2), commuting distance (X_4), and wages (X_5) significantly affect the productivity of harvest employees at PT. Agronusa Bumi Lestari at α 5%.